THE DISQUALIFICATION OF COMPANY DIRECTORS AND ITS EFFECT ON ENTREPRENEURSHIP - Shopovski, Jovan; Bezzina, Frank; Zammit, Martin M. (European Scientific Journal, ESJ, 2013)
﻿The disqualification of directors or members of the management of a company, expressed as a prohibition for these persons to manage or take part in the management of the companies, is a highly significant Act of Company Law, which is implemented in many legislatures around the world. Utterly restrictive in its nature, it applies to the directors and members of the management team, and in some legislation systems even to the capital owners of the companies whose illegal actions initiate its application. The activation of this institution in precisely determined situations most often results in the prohibition of a particular person to manage a company for a definite period of time. These restrictive measures are effected with the purpose of establishing certain control in trading, while imposing limitations to a certain focus group. In its nature, these measures differ from those brought into effect in order to instigate entrepreneurship. For entrepreneurship in a given country to flourish would necessitate the realization of a liberalized regulation of the market. This paper focuses on the impact that this restrictive institution has in practice, and whether it is in fact achieving the objective(s) for which it was legally established. Particular attention is given to the adverse consequences that directors’ disqualification may bring on entrepreneurial freedom and innovation, and how this in turn could influence directly or indirectly economic growth or in weathering the recessional storm(s).